2021
DOI: 10.3390/catal11020216
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Transformation of 5-Hydroxymethylfurfural into 2,5-di(hydroxymethyl)furan by a Newly Isolated Fusarium striatum Strain

Abstract: The compound 2,5-di(hydroxymethyl)furan (DHMF) is a high-value chemical block that can be synthesized from 5-hydroxymethylfurfural (HMF), a platform chemical that results from the dehydration of biomass-derived carbohydrates. In this work, the HMF biotransformation capability of different Fusarium species was evaluated, and F. striatum was selected to produce DHMF. The effects of the inoculum size, glucose concentration and pH of the media over DHMF production were evaluated by a 23 factorial design. A substra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There are some reports in the literature describing the production of BHMF by wholecell biocatalysts. To the extent of our knowledge, the BHMF yield reported in our work (99.65%) is the highest reported for yeast [43][44][45], bacteria [46,47], and fungi [48,49] in batch and fed-batch modes using a synthetic medium with glucose as co-substrate. Specifically, in yeast, Li et al (2016) reported BHMF production at 35 • C by Meyerozyma guilliermondii SC1103 from 100 mM of HMF with an inoculum of 20 g/L of wet weight using glucose as a co-substrate and obtained a yield of 86% [43].…”
Section: Discussionmentioning
confidence: 54%
“…There are some reports in the literature describing the production of BHMF by wholecell biocatalysts. To the extent of our knowledge, the BHMF yield reported in our work (99.65%) is the highest reported for yeast [43][44][45], bacteria [46,47], and fungi [48,49] in batch and fed-batch modes using a synthetic medium with glucose as co-substrate. Specifically, in yeast, Li et al (2016) reported BHMF production at 35 • C by Meyerozyma guilliermondii SC1103 from 100 mM of HMF with an inoculum of 20 g/L of wet weight using glucose as a co-substrate and obtained a yield of 86% [43].…”
Section: Discussionmentioning
confidence: 54%
“…Different approaches can be taken to overcome the toxic effect, such as increasing the inoculum size of the cells by adding more discs or the inoculation in the form of spores. 22 To that end, the inoculation of the fungus from a suspension of spores was assessed. However, there was HMF reduction to DHMF with high yields (data not shown), indicating that the way of inoculation of the fungus has a significant effect on the HMF biotransformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…28,32 The capability of F. culmorum EAN51 to biotransform HMF into an unknown compound was previously reported in a screening of different Fusarium species. 22 This compound was further identified as DFF; however, the yield and selectivity obtained were low and far from optimal. In this work, the capability of this fungus to produce DFF is assessed by evaluating the effect of different nitrogen sources and through optimization of the concentration of peptone and glucose in the culture medium through RSM.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungus Aureobasidium subglaciale F134 was identified for the production of BHMF, reaching the highest reported productivity of 28.7 mM/h with a fed-batch process [27]. Another fungus, Fusarium striatum, was reported to produce 145 mM of BHMF with high yield of 97% [28]. The bacterium Burkholderia contaminans NJPI-15 reached the highest BHMF titer of 656 mM in a fed-batch with 94% yield [29].…”
Section: 5-bis(hydroxymethyl)furan (Bhmf)mentioning
confidence: 99%